Immune Inspired Framework for MANETs’ Security - Yasir Abdelgadir , Mohamed; Azween, Abdullah (2008)
-As a comprehensive security system, researchers recently had turned to the human immune system as a very wealthy inspiration source. DNA computation, evolutionary computation, artificial neural networks, and artificial immune systems are some of the researcher interest which can be pointed out. By means of diverse kind of cells, molecules, and mechanisms, the immune system efficiently protects the human body against different kinds of attacks. Many immune-inspired techniques have been developed with the aim to settle different engineering computer problems. Networking security is representing one of the most significant fields that immune-inspired techniques have been applied to. Given that mobile ad hoc networks have a decentralized nature more similar to the human immune system (HIS); immune-inspired security architecture is highly expected to come across different ad hoc security problems; one of which is the malicious node that can disrupt the routing process, masquerade the legitimate nodes, and impersonate the trusted nodes. In this paper, immune-inspired security architecture for stimulating a number of HIS processes for securing mobile ad hoc networks has been presented. Both, the negative selection and danger theory techniques have been combined along with many other inspired processes so as to come up with scalable a d robust system. Distributability, second response, self recovery, is the hallmarks of the proposed architecture which put a consideration on high nodes